The Role of Parental Involvement in Student Academic Outcomes - Alma Yulia Utami (Journal of Education Review Provision, 2022)
It has been demonstrated that parental involvement in a student's academic life improves the student's performance. Assisting with schoolwork, joining in extracurriculars, and talking to teachers are all examples of ways to get involved in the classroom. Parents who are actively interested in their children's education have been linked to improved academic performance, improved school attendance, and increased participation in advanced courses. Increased parental participation has been linked to improved school attitudes and increased academic motivation in children. A student's academic performance may be hindered by socioeconomic or familial problems, yet parental participation can act as a buffer against these influences. Efforts to engage and assist parents in their child's education can have a long-lasting, beneficial effect on a student's academic and personal development, and parents' involvement plays a substantial role in students' academic outcomes.